PELATIHAN PENGOLAHAN DATA PENELITIAN BISNIS PADA MAHASISWA SEKOLAH TINGGI ILMU EKONOMI WIYATAMANDALA DENGAN MENGGUNAKAN APLIKASI SPSS (STATISTICAL PRODUCT AND SERVICE SOLUTIONS) - Andres Dharma Nurhalim; Rohmanuddin Rohmanuddin (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2022)
In data processing activities, it is known that there are still many students who do not understand the SPSS program in processing the data used to compose their final project. This is experienced by students of the management and accounting study program at the Wiyatamandala School of Economics where there are still many who do not understand how to operate the SPSS program. Therefore, it is necessary to introduce technology-based learning media related to the SPSS program through training. This training is part of community service activities that aim to provide additional knowledge, improve skills, train students' creative thinking and make it easier to determine the statistical tests used in compiling the final project. After the training was completed, the students seemed very enthusiastic, many of them even asked questions. Students also gave a good appreciation of the training activities and hoped that more activities related to data analysis would be held in the future. This training activity gives more value to students, especially in completing their final project